Wellness policy and the inappropriate use of food rewards within youth settings - Warner, Ninette (Kansas State University, 2020)
There is evidence showing that the use of food rewards can contribute to chronic emotional overeating, increased calorie intake, weight gain, poor self-regulation of food intake, disordered eating, changes in reward circuitry within the brain, and increased preference for high- fat, high- sugar foods. The bidirectional nature, or the extent to which these associated negative outcomes are a consequence of, or were present before, the use of food rewards is undetermined. Most research studies on this topic are observational in nature, with some conflicting results. Under the Healthy Hunger-Free Kids Act of 2010 (HHFKA), schools participating in the National School Lunch Program are required to have wellness policies that meet minimum standards for proper nutrition. Under this act, all school meals and snacks provided to students need to adhere to the United States Department of Agriculture (USDA) nutrition guidelines; this includes all foods made available to students during the school day such as classroom snacks brought by parents, food for classroom parties and events, or other foods given as incentives for good behavior or success. Research indicates that schools with active wellness teams that include a variety of members who are actively engaged in wellness policy implementation are more likely to have strongly written policies with better implementation compared to schools with fewer wellness team members and activity within schools. It is imperative that parents, adult caregivers, and educators understand the negative consequences associated with using food rewards, and are knowledgeable about and use alternative non-food-based strategies to encourage and reward children.
Keywords: Food rewards; School wellness policy